Effects of Somatotropic Axis Gene Polymorphisms on Milk Yields in Simmental Cattle - Sonmez, Z; Kopuzlu, S; Özdemir, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Due to the increasing world population, scientists aim to obtain high-yield products using new techniques and methods to meet needs in the fields of food, agriculture, and livestock. It is very important to selected the candidate genes and markers correctly, especially in the QTL and MAS techniques in livestock. Somatotropic axis genes affect yield traits, growth, reproduction, and milk production in cattle. In the study, we determined GH/AluI and IGFI/SnaBI gene polymorphisms using the PCR-RFLP technique in DNA samples obtained from 70 Simmental cattle. The allele frequencies of the genes were in the same proportion as 0.62 and 0.38, L and V for the GH gene and T and C for the IGFI gene. There was no significant relationship between the polymorphic genotypes of the genes we examined and lactation milk yields, 305-day milk yields, daily milk yields, and lactation periods of Simmental cattle. The probability of using bGH/AluI and IGFI/SnaBI genetic variations as markers in association studies with milk yield in cattle is extremely low. Keywords: Axis genes; RFLP; MAS; Simmental; milk yield